Indigenous Knowledge and Forest Succession Management in the Brazilian Amazon: Contributions to Reforestation of Degraded Areas - Schmidt, Marcus Vinícius C.; Ikpeng, Yakuna Ullillo; Kayabi, Tariaiup; Sanches, Rosely Alvim; Ono, Katia Yukari; Adams, Cristina (Frontiers in Forests and Global Change, 2021)
The indigenous systems of agricultural and forest management in the Amazon are characterized by a deep knowledge of ecological processes, biodiversity, and the use and management of fire. The influence of these systems on the distribution of biodiversity includes semi-domesticated and domesticated species and landscapes, which have led to extensive anthropogenic or cultural forests. However, in many places, the livelihoods of indigenous peoples are being transformed by the intensification of agriculture and social, ecological, and economic changes, putting at risk the sustainability of production systems and food security and sovereignty of these peoples. In the last years, in the Xingu Indigenous Territory (XIT), the food production systems and the form of occupation of territories have changed, affecting the recovery of secondary forests, which now demand a too long period. The increase in the number and frequency of fires has aggravated this situation, due to a drier climate that has become predominant in the region. Changes in climate are attributed to deforestation in the neighboring municipalities, especially in the headwaters of the Xingu river basin. This study was conducted among the Kawaiwete (Tupi-Guarani) and the Ikpeng (Carib-Arara) peoples in the XIT, in the state of Mato Grosso, Brazil. The main objective was to develop alternative techniques of forest management based on indigenous and scientific knowledge more adapted to the new livelihood contexts, aiming to favor forest regeneration in areas dominated by shifting cultivation. We sought to answer the following questions: (I) How do forests regenerate during the fallow period? (II) How can local management improve forest regeneration? (III) Are there indicator species for secondary succession, soil recovery, and vulnerability to fires? (IV) Is the increase in the number of fires affecting the sustainability of the shifting cultivation systems? Our results show that some local practices based on indigenous knowledge have the potential to facilitate natural regeneration, such as choosing forest areas that have been recovered for agricultural use, limiting the number of cultivation cycles, protecting and selecting of individual trees during cultivation period, and attracting seed dispersers. Assisted natural regeneration strategies grounded on indigenous knowledge are promising ways to restore degraded lands of the XIT.